Analyse und Beschreibung des mechanischen Werkstoffverhaltens von presshärtbaren Bor-Manganstählen - Stöhr, Thomas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)
In the scope of this work was the improvement of the accuracy of FE models with regard to forming processes following the temperature-time profile of the hot stamping process. The focus of the investigations was on the determination and description of the forming behavior of boron manganese steels in dependency of process relevant influencing factors. Furthermore a methodology for the determination of true stress-strain curves at elevated temperatures in the layer compression test had been determined, enabling the rating of the stress state on the forming behavior of boron manganese steels. The distinctive improvement of the quality of the FE modeling of hot stamping processes utilizing the knowledge of this work had been shown in a comparison of the sheet thickness evolution of a numerically mapped and a experimentally formed componen

Analytic Methods for the Calculation of the Heat Transfer Coefficient - Merklein, Marion; Wieland, Michael; Stöhr, Thomas; Lechler, Jürgen; Grüner, Martin (International Review of Mechanical Engineering, 2010)
In the product development cycle numerical simulations are commonly used for the process layout. In case of hot stamping the process layout gets quite complex because material's thermal and mechanical properties have to be taken into account. Hot stamping can be explained as forming and quenching in one process step and therefore the knowledge of thermal properties is indispensable to fulfill the opposing requirements of a good heat flux with respect to a good energy balance of the tool. A description of this energy exchange between the hot blank and the tool is given by the heat transfer coefficient. The determination of the heat flux under process relevant conditions for hot stamping is influenced by several variables. Within the scope of this work, these different variables are compared using two analytical methods to calculate the heat transfer coefficient based on the same measurement data. Furthermore the advantage of these analytical methods and the possibility of improvement is shown up. At least a validation of the calculated heat transfer coefficients by simulation is presented. Copyright © 2010 Praise Worthy Prize S.r.l. - All rights reserved.
LFT Import::2019-07-29 (224)
Keywords: Heat transfer coefficient; Hot stamping

Basic Investigations on Hot Stamping of Tailor Welded Blanks Regarding the Manufacturing of Lightweight Components with Functionally Optimized Mechanical Properties - Lechler, Jürgen; Stöhr, Thomas; Kuppert, Andreas; Merklein, Marion (Transactions of the North American Manufacturing Research Institute of SME, 2010)
The combination of two innovative technologies, the application of tailored products on the one hand and hot sheet metal forming on the other, allows to achieve final component properties, that could not be realized so far. Within this work major research activities are described concerning material engineering, which have been carried out within the scope of component and process development of hot stamping of tailor welded blanks (TWB). This includes basic analyses related to the selection of an appropriate steel grade. For the finally selected and with an aluminum-silicon layer pre-coated steel grade HX340 LAD+AS150 investigations have been performed to determine the thermo-mechanical properties of the material subject to the most important process parameters during hot stamping. In addition special emphasis is placed on the description of the weld seam properties and the forming and failure behavior of hot stamping TWBs under process relevant conditions.
LFT Import::2019-07-29 (1161)
Keywords: 22MnB5; Hot stamping; HX340 LAD+AS150; Mechanical properties; Tailor welded blanks

Beschreibung des mechanischen Werkstoffverhaltens beim Warmumformen höchstfester Stähle - Stöhr, Thomas; Merklein, Marion (Tagungsband 5. Erlanger Workshop Warmblechumformung, 2010)
LFT Import::2019-08-05 (744)

Characterization of tribological and thermal properties of metallic coatings for hot stamping boron-manganese steels - Merklein, Marion; Lechler, Jürgen; Stöhr, Thomas (Tagungsband The Coatings, 2008)
LFT Import::2019-08-05 (194)

Determination of frictional and thermal characteristics for hot stamping with respect to a numerical process design - Stöhr, Thomas; Merklein, Marion; Lechler, Jürgen (Proceedings 1st International Conference Hot Sheet Metal Forming of High-Performance Steel - CHS2, 2008)
LFT Import::2019-08-05 (213)

Einfluß unterschiedlicher Wärmebehandlungsrouten auf die Robustheit und Höhe der mechanischen Eigenschaften des Stahls 22MnB5 - Glatzer, M.; Stöhr, Thomas; Merklein, Marion; Sikora, S. (Tagungsband 4. Erlanger Workshop Warmblechumformung, 2009)
LFT Import::2019-08-05 (218)

Herstellung von funktionsoptimierten Bauteilen im Presshärtprozess - Merklein, Marion; Lechler, Jürgen; Stöhr, Thomas; Svec, Thomas (Stahl und Eisen, 2010)
LFT Import::2019-07-29 (225)

Interlaboratory comparison for heat transfer coefficient identification in hot stamping of high strength steels - Bosetti, Paolo; Bruschi, S.; Stöhr, Thomas; Lechler, Jürgen; Merklein, Marion (Proceedings of Esaform 2010, 2010)
The topic of the paper is the identification of the heat transfer coefficient (HTC) in hot stamping of boron steel sheets under conditions very close to the industrial ones. Two approaches followed by one lab in Germany and one lab in Italy are presented for HTC identification, showing the two experimental apparatuses that were set-up to conduct the tests, the procedures developed and applied to identify the HTC. The obtained results are compared in terms of dependence of HTC from the applied contact pressure, the similarities and the differences of the two approaches are outlined and commented. © 2010 Springer-Verlag France.
LFT Import::2019-08-05 (223)
Keywords: Heat transfer coefficient; Hot stamping; Inverse analysis

Interlaboratory Comparison of Friction Conditions in Hot Stamping Operations - Borsetto, F.; Ghiotti, Andrea; Bruschi, S.; Stöhr, Thomas; Lechler, Jürgen; Merklein, Marion (Key Engineering Materials, 2010)
The paper presents results obtained at two labs, on in Germany and one in Italy, in terms of friction coefficient as function of hot stamping process parameters. Even if the testing procedures and analysis tools to evaluate tribological conditions are different for the two labs, both the approaches show a similar trend as regards the friction coefficient dependence from the process parameters. © (2010) Trans Tech Publications.
LFT Import::2019-07-29 (1160)
Keywords: High strength steel; Hot stamping; Tribology

Investigations on different strategies for influencing the microstructural properties with respect to partial hot stamping - Stöhr, Thomas; Lechler, Jürgen; Merklein, Marion (Proceedings 2nd International Conference Hot Sheet Metal Forming of High-Performance Steel - CHS², 2009)
LFT Import::2019-08-05 (215)

Investigations on Parameters Influencing Thermal and Frictional Properties within Hot Stamping - Merklein, Marion; Stöhr, Thomas; Svec, Thomas; Wieland, Michael (Journal of Heat Treatment and Materials, 2011)
LFT Import::2019-07-29 (1772)
Keywords: Abrasive wear; Adhesive wear; Heat tnmsler; Hot stamping; Jriclion

Investigations on the Flow Behavior of Boron-Manganese Steels at elevated strain rates - Stöhr, Thomas; Merklein, Marion (Proceedings 3rd International Conference on Hot Sheet Metal Forming of High-Performance Steel, 2011)
LFT Import::2019-08-05 (1736)

Investigations on the thermal behavior of ultra high strength boron manganese steels within hot stamping - Merklein, Marion; Lechler, Jürgen; Stöhr, Thomas (International Journal of Material Forming, 2009)
LFT Import::2019-07-29 (221)

Maßgeschneidert – Funktionsoptimierte Strukturbauteile im Presshärtprozess - Merklein, Marion; Svec, Thomas; Stöhr, Thomas; Wieland, Michael (Lightweight Design, 2010)
LFT Import::2019-07-29 (718)

Prognose der mechanischen Bauteileigenschaften bei Presshärtprozessen anhand mikrostruktureller und umformtechnischer Zusammenhänge - Springer, R.; Lechler, Jürgen; Stöhr, Thomas; Karbasian, H.; Schaper, M.; Merklein, Marion; Brosius, A.; Tekkaya, A.E. (Tagungsband 3. Erlanger Workshop Warmblechumformung, 2008)
LFT Import::2019-08-05 (196)

Some aspects concerning the physical models obtained using high performance composite material - Nedelcu, D.; Stöhr, Thomas; Ciofu, C.; Mindru, D (Proceedings 13th International Conference ModTech, 2009)
LFT Import::2019-08-05 (216)

Thermo-Mechanical Properties of Tailor Welded Blanks in Hot Sheet Metal Forming Processes - Lamprecht, K.; Deinzer, G.; Stich, A.; Lechler, Jürgen; Stöhr, Thomas; Merklein, Marion (Proc. 50th Conference of IDDRG 2010, 2010)
LFT Import::2019-08-05 (226)

Thermo-mechanical sheet metal forming of aero engine components in Ti-6Al-4V–PART 1: Material characterisation - Odenberger, E.-L.; Hertzman, J.; Thilderkvist, P.; Merklein, Marion; Kuppert, Andreas; Stöhr, Thomas; Lechler, Jürgen; Oldenburg, M. (International Journal of Material Forming, 2012)
LFT Import::2019-07-29 (1838)

Tool development based on modelling and simulation of hot sheet metal forming of Ti-6Al-4V titanium alloy - Odenberger, E. -L.; Oldenburg, M.; Thilderkvist, P.; Stöhr, Thomas; Lechler, Jürgen; Merklein, Marion (Journal of Materials Processing Technology, 2011)
In the aero engine industry alternative manufacturing processes for load carrying aero engine structures imply fabrication. The concept of fabrication involves simple forgings, sheet metals and small ingots of e.g. titanium alloys which are welded together and heat treated. In the concept phase of the product development process, accurate evaluations of candidate manufacturing processes with short lead times are crucial. In the design of sheet metal forming processes, the manual die try out of deep drawing tools is traditionally a time consuming, expensive and inexact process. The present work investigates the possibility to design hot forming tools, with acceptable accuracy at short lead times and with minimal need for the costly die try out, using finite element (FE) analyses of hot sheet metal forming in the titanium alloy Ti-6Al-4V. A rather straightforward and inexpensive approach of material modelling and methods for material characterisation are chosen, suitable for early evaluations in the concept phase. Numerical predictions of punch force, draw-in and shape deviation are compared with data from separate forming experiments performed at moderately elevated temperatures. The computed responses show promising agreement with experimental measurements and the predicted shape deviation is within the sheet thickness when applying an anisotropic yield criterion. Solutions for the hot forming tool concept regarding heating and regulation, insulation, blank holding and tool material selection are evaluated within the present work. © 2011 Elsevier B.V. All rights reserved.
LFT Import::2019-07-29 (1690)
Keywords: FEM simulation; Hot forming test; Hot sheet metal forming; Ti-6Al-4V; Titanium alloys; Validation

Weiterführende Untersuchungen zum Fließverhalten presshärtbarer Stähle - Stöhr, Thomas; Merklein, Marion (Tagungsband 4. Erlanger Workshop Warmblechumformung, 2009)
LFT Import::2019-08-05 (217)